Supplementation of cereal straws with different protein feeds: In vitro studies - Moreira O.M.S.C.; Ribeiro J.M.C.R. (Exploitation of Mediterranean roughage and by-products, 1998)
Samples of the diets tested in 3 growth trials with lambs which were carried out at the Dipartimento di Scienze Zootecniche, our partner in Italy, were submitted to in vitro ruminal degradation in a semi-continuous fermentation system (RUSITEC). The aim of the study was the comparison between different protein feeds included in complete balanced diets, based on wheat straw, for growing lambs. The studied protein feeds were: Soya bean meal (SBM), meat meal (MM), sunflower cake (SFC), coconut cake (CNC), brewers yeast (BY), fish meal (FM), blood meal (BM) and an industrial product with its protected protein (PP) from microbial attack, introduced at increasing levels of replacement of crude protein. The results clearly indicate that the diet with SBM was the most degradable. The diets with CNC and BM gave the highest and the lowest C2 per C3 ratio, respectively. The diet with MM permitted the highest microbial protein yield (MPY). In the diets with the protected protein, the nitrogen degradation was only affected by the level of replacement and of crude protein and the best C2 per C3 ratios were those of 30 per cent protected protein and 18 per cent crude protein.